Soundscape of Nansen Basin – Central Arctic Ocean - Mohanta, Sunil Kumar; Sanjana, M.C.; Ganesan, Latha; Elangovan, Arunbabu; Raja, Kannan (Archives of Acoustics, 2026)
This work mainly focuses on a deepwater soundscape study in the Nansen Basin, Central Arctic Ocean, by using Ambient Noise Measurement System (ANMS) data, which was deployed as part of the Nansen Environmental and Remote Sensing Center (NERSC-4) mooring from September 2019 to July 2020. The main objective of the work is to study the sources of underwater noise of the Central Arctic Ocean (CAO) along with their characteristic patterns. Also in this work, the seasonal variation of the sound pressure level of CAO is studied. The seasonal variation of the sound pressure level of the CAO is maximum in summer, and the minimum seasonal variation was observed during spring. The difference in seasonal variability in 1/3 octave band frequencies between summer and spring was 4.1 dB (re 1 μPa²/Hz). Shipping and marine species are the most dominant noise sources of the Central Arctic Ocean. Bowhead whales and bearded seals are the most common marine species observed in this location. The bearded seal vocalisation is more intense between 300 and 700 Hz. Bowhead whales produce two different types of simple calls i.e., sound patterns : one is S-moans, and the other is V-moans. The S-moan patterns are mainlydominated by low frequencies i.e., below 600 Hz. The V-moans patterns are dominated in the frequency range of 300 to 1230 Hz. The killer whales are also observed in the study location, which represents a shifting Arctic environment. The soundscape generated by killer whales is observed between 160 Hz and 2 kHz.